The Mysteries of Mystery Snails Facts and Myths. - Mackie, Gerry (Cambridge Scholars Publishing, 2022)
This book offers a comprehensive review of the literature on Chinese and Japanese mystery snails around the globe, providing details of their distribution in 10 continents and more than 130 countries. It discusses several fascinating facts on dispersal mechanisms, biology, ecology, impacts, and control, revealed from more than 900 peer-reviewed articles. The Chinese Mystery Snail has been in North America now for more than 130 years, and is the second oldest introduced freshwater mollusc species from Eurasia, the oldest being the Faucet Snail, Bithynia tentaculata, introduced in 1870. The scie.